Cognitive deficits for facial emotions among male adolescent delinquents with conduct disorder - Kou, Hui; Luo, Wei; Li, Xue; Yang, Ye; Xiong, Min; Shao, Boyao; Xie, Qinhong; Bi, Taiyong (Frontiers in Psychiatry, 2022)
According to the social-cognitive theory and the social-information-processing theory, individuals with conduct disorder, a persistent and repetitive pattern of problematic behavior, might have cognitive biases towards hostile facial expressions. However, according to the optimal stimulation/arousal theory, the stimulation-seeking theory and the fearlessness theory, individuals with conduct disorder might have less fear and show less response to hostile or threatening facial expressions. To reconcile the discrepancy, we examined the cognitive biases including attentional processing and working memory processing to emotional faces among adolescents with conduct disorder. 35 male adolescent delinquents with conduct disorder and 35 age-matched delinquents without conduct disorder completed a visual search task and a delayed-match-to-sample task to examine their attentional processing and working memory processing for sad, angry, happy, and fearful faces, respectively. It was found that conduct disordered individuals searched angry and fearful faces, rather than sad and happy faces, more slowly than individuals without conduct disorder. However, no difference in mnemonic processing for facial emotions was found between groups. The results indicated that male adolescent delinquents with conduct disorder showed deficits in attentional orientation to hostile and threatening faces, supporting the optimal stimulation/arousal theory, the stimulation-seeking theory and the fearlessness theory, but not the social-cognitive theory.